THE RETURN OF GREAT POWERS : RUSSIA, CHINA, AND THE NEXT WORLD WAR - Sciutto, Jim (Dutton, 2024)
"The fall of the Berlin Wall in 1989 dawned what Francis Fukuyama called "The End of History." Three decades later, Jim Sciutto said on CNN's air as the Ukraine war began, that we are living in a "1939 moment." History never ended-it barely paused-and the global order as we have known it is now gone. Great powers are reinvigorated and determined to assert dominance on the world stage. And as it escalates, this new order will affect everyone across the globe. Peace has been shattered by Russia's invasion of Ukraine, but in reality, this affects every corner of our world-from Helsinki to Beijing, from Australia to the North Pole. This is a battle with many fronts: on the Arctic floor, in the oceans and across the skies, and in cyberspace. Sciutto argues that we are witnessing the return of great power conflict, "a definitive break between the post-Cold War era and an entirely new and uncertain one." The world order that marked the last thirty years is shifting, and Sciutto details the realities of this new post-post-Cold War era, the increasingly aligned Russian and Chinese governments, and the flashpoint of a new, global nuclear arms race. With savvy, thorough reporting, he follows-up his 2019 bestseller, The Shadow War: Inside Russia's and China's Secret Operations to Defeat America, which focused on the covert tactics of a hidden conflict. The Return of Great Powers is an analysis of a historic and visible shift in real time. And it poses a question: that as we consider uncertain outcomes, we ask whether the West and Russia and China can prevent a new World War"--